Seroprevalencia de Hepatitis B en donantes de sangre de la Ciudad de Maracaibo, Estado Zulia. Periodo 2000-2005 - Pozo Elieth; Chaparro Melissa; Padrón, Ana (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2007)
Abstract: Hepatitis B is a serious disease caused by a DNA virus that attacks the liver. The infection may either be acute or chronic. Hepatitis B is transmitted through exposure to bodily fluids containing the virus. This includes unprotected sexual contact, blood transfusions, re-use of contaminated needles and syringes, vertical transmission from mother to child during childbirth, and so on. To investigate the seroprevalence of the viral infection caused by the hepatitis B virus, the sera from a group of 46.563 blood donors was evaluated. These donors were apparently healthy, between 18 and 60 years old, male or female, and came to the "Instituto Hematológico de Occidente, Banco de Sangre" in Maracaibo from January 2000 to December 2005. Laboratory evaluation included third-generation ELISA tests to detect viral surface antigens (HBs-Ag) and total antibodies for the hepatitis B core antigen (Anti-HBc), and thereby discard infection in the donors. A total of 1.439 (3.09%) cases were seropositive for Anti-HBc, which corresponds to the real seroprevalence, since the marker found in this group indicates past infections. 97 (0.208%) sera where found to be positive for HBs-Ag, indicating incidence or new cases. However, 95 (0.205%) sera had both HBs-Ag and Anti-HBc positive, which means that both markers were present in each of these 95 donors and this could be a motive for the development of acute or chronic diseases. 95.16% of the positive sera where taken from male patients and the larger prevalence (32.42%) is between the ages of 29 through 39 years old. This data was analyzed using the ji-squared test which revealed that there is no statistical significance for the differences found. These results show the importance of applying educational campaigns related to Hepatitis B infection to the population attending this health center, which will hopefully lead to prevention of this disease. Likewise, it is important to optimize the laboratory procedures used to identify infectious diseases like hepatitis B. Resumen: Con la finalidad de conocer la seroprevalencia de la infección por el virus B de la hepatitis en donantes de sangre se evaluó un grupo de 46,563 pacientes aparentemente sanos, entre 18 y 60 años edad, de ambos sexos, que acudieron al Instituto Hematológico de Occidente, Banco de Sangre de la Ciudad de Maracaibo en el período comprendido entre enero del año 2000 a diciembre del año 2005. La evaluación de laboratorio incluyó pruebas de ELISA de tercera generación para detectar Antígeno de Superficie y Anticuerpos totales frente al Core y así descartar la infección en los donantes. Se obtuvieron 1,439 casos positivos (3,09%) para los Anticuerpos frente al Core, lo que corresponde a la seroprevalencia real, ya que el marcador encontrado en este grupo indica infección pasada; así también 97 casos con Antígeno de Superficie positivo (0,208%) lo cual corresponde a incidencia o casos nuevos; y 95 casos positivos para ambos marcadores en un mismo donante (0,204%) los cuales podrían ser motivo de infecciones agudas o crónicas. Se encontró que el 95,16% de casos positivos corresponden al sexo masculino, y que la mayor prevalencia (32,42%) oscila en donantes con edades comprendidas entre 29 y 39 años. Estos datos fueron analizados estadísticamente mediante la prueba del Ji-cuadrado el cual reveló que no existen diferencias significativas en los resultados obtenidos. Todo lo anterior indica la importancia de implementar métodos educativos en relación a esta infección en la población atendida en este centro, lo cual permitirá la prevención acertada de esta enfermedad; de igual manera los procedimientos de laboratorio deben estar enfocados hacia la optimización en el descarte de las enfermedades infecciosas como la hepatitis B.